2018
DOI: 10.1111/tpj.13800
|View full text |Cite
|
Sign up to set email alerts
|

Plant behaviour under combined stress: tomato responses to combined salinity and pathogen stress

Abstract: SUMMARYCrop plants are subjected to a variety of stresses during their lifecycle, including abiotic stress factors such as salinity and biotic stress factors such as pathogens. Plants have developed a multitude of defense and adaptation responses to these stress factors. In the field, different stress factors mostly occur concurrently resulting in a new state of stress, the combined stress. There is evidence that plant resistance to pathogens can be attenuated or enhanced by abiotic stress factors. With stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
110
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(126 citation statements)
references
References 115 publications
0
110
0
Order By: Relevance
“…The activity of SOD, POD, APX and CAT was significantly increased in PI while it was reduced in R95 cultivar when treated with WS, HS, and WS+HS. The activities of GR were significantly higher in all three types of stresses in both Plants' responses to concurrent stresses often occurring in the field are very exclusive, when compared to individual stress treatments and will display cross-tolerance to better adapt to those stresses (54)(55). We report the result of our studies on two contrast soybean cultivars to determine the physiological and molecular mechanism for cross-tolerance between multiple stresses.…”
Section: Determination Of Enzymes Activitiesmentioning
confidence: 91%
“…The activity of SOD, POD, APX and CAT was significantly increased in PI while it was reduced in R95 cultivar when treated with WS, HS, and WS+HS. The activities of GR were significantly higher in all three types of stresses in both Plants' responses to concurrent stresses often occurring in the field are very exclusive, when compared to individual stress treatments and will display cross-tolerance to better adapt to those stresses (54)(55). We report the result of our studies on two contrast soybean cultivars to determine the physiological and molecular mechanism for cross-tolerance between multiple stresses.…”
Section: Determination Of Enzymes Activitiesmentioning
confidence: 91%
“…a single stress condition vs its control), there is a knowledge gap in the identification of QTLs involved in responses to combined stress. This aspect is of capital importance as it was shown that stress combination in tomato (biotic and/or abiotic) does not always have an additive effect regarding physiological, morphological, or biochemical responses compared with single stress (Rivero et al ., ; Bai et al ., ; Martinez et al ., ).…”
Section: Discovery Of Genetic Variations Underlying Major Traits In Tmentioning
confidence: 97%
“…Tomato (Solanum lycopersicum) is one of the most commonly cultivated vegetables in the world (http://faostat.fao.org), and it also serves as a model plant for studying plant-microbe interactions [21]. Ebb-and-flow systems have been used widely for the commercial cultivation of tomato plug seedlings because of its notable advantages.…”
Section: Introductionmentioning
confidence: 99%